Bioinformatics: databases,tools,algorithms - Bosu, Orpita (Oxford University Press, 2010)
Bioinformatics: databases,tools,algorithms / Bosu, Orpita. -- New Delhi: Oxford University Press, 2010 660.6 B745 No. of Copies : 1